2021
DOI: 10.1093/jxb/erab510
|View full text |Cite
|
Sign up to set email alerts
|

CmFSI8/CmOFP13 encoding an OVATE family protein controls fruit shape in melon

Abstract: Summary Fruit shape is an important quality and yield trait in melon. Although some fruit shape-related QTLs have been reported in melon, the target genes and the underlying mechanism remain poorly understood. Here, we identified and characterized a gene controlling fruit shape from two melon inbred lines B8 and HP22. Genetic analysis suggests that the fruit shape was controlled by a single and incompletely dominant locus, designated CmFSI8/CmOFP13. The CmFSI8/CmOFP13 gene was finely mapped to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…This QTL was assigned as a consensus FS4.1 [ 1 ] due to the fact that it has been reported in a number of populations, including Gy14 × 9930 RILs [ 2 ], S1000 × S1002 F 2:3 families [ 28 ], WI7167 × WI7200 F 2:3 families [ 29 ], and CS-PMR1 × Santou RILs [ 30 ]. The cucumber FS4.1 is syntenic to the melon CmFSI8, whose underlying causal gene is CmOFP1a/CmOFP13 [ 1 , 7 , 31 ]. Thus, the CsOFP1a might be considered a top candidate for FS4.1 .…”
Section: Discussionmentioning
confidence: 99%
“…This QTL was assigned as a consensus FS4.1 [ 1 ] due to the fact that it has been reported in a number of populations, including Gy14 × 9930 RILs [ 2 ], S1000 × S1002 F 2:3 families [ 28 ], WI7167 × WI7200 F 2:3 families [ 29 ], and CS-PMR1 × Santou RILs [ 30 ]. The cucumber FS4.1 is syntenic to the melon CmFSI8, whose underlying causal gene is CmOFP1a/CmOFP13 [ 1 , 7 , 31 ]. Thus, the CsOFP1a might be considered a top candidate for FS4.1 .…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of CsOFP12-16c from cucumber ( Cucumis sativus ) in Arabidopsis affects the silique development and causes blunt and shorter siliques ( Han et al, 2022 ). Previous studies have also suggested that CmOFP13 may control the fruit shape in melon ( Cucumis melo ) ( Monforte et al, 2014 ; Ma et al, 2021 ). Also, the expression of MaOFP1 was reported to be negatively associated with fruit ripening in banana ( Musa paradisiaca ) ( Liu et al, 2015b ).…”
Section: Introductionmentioning
confidence: 94%
“…This cellular mechanism of shape explains why the morphology of disparate organs such as tubers and grains are controlled by genes of the same three families. As highlighted above, natural variation of organ shape in diverse crops including rice ( GW7/GL7 (orthologue of AtTRM1 , Wang et al, 2015c ; Wang et al, 2015d ), maize (maize ZmLNG1 , homolog of Arabidopsis TRMs ; Wang et al., 2022b ), potato tuber ( StOFP20 ( Wu et al., 2018 ), cucumber CsTRM5 ( Wu et al., 2018 ; Wang et al, 2020a, b ), CsSun ( Pan et al., 2017 , Wang et al, 2020a, b ), pepper CaOvate ( Tsaballa et al, 2011 ), CaOFP20 ( Borovsky et al 2022 ), CaTRM25 ( Taitano, 2020 ), melon CmOFP13 ( Wu et al, 2018 , Ma et al, 2022a , Martínez-Martínez et al., 2022 ), watermelon ClSUN25-26-27a ( Dou et al., 2018 ; Legendre et al., 2020 ), pummelo CitOFP19 ( Wu et al., 2022 ) and peach PpOFP2 ( Guan et al., 2021 ).…”
Section: Developmental Aspects Of Shape Regulation and Common Genetic...mentioning
confidence: 99%